PRELIMINARY STUDY OF THE POTENCY OF SEDIMENTATION RATE IN BANJIR KANAL TIMUR SEMARANG COASTAL WATERS - Tonny Bachtiar (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Five sets of sediment traps were installed for thirty days (Oct.- Nov. 1999) in Banjir Kanal Timur Semarang coastal waters to examine the potency of sedimentation rate. Two sediment traps were lost in the second week of measurement. Based on the average data of three sets of sediment traps, the potency of sedimentation rate in Banjir Kanal Timur Semarang coastal waters was 6.10 cm/month. The result did not reflect the fact of the field condition. Based on the correction made on the input of suspended discharge into Banjir Kanal Timur Semarang coastal waters and the average area of sediment distribution, the potency of sediment rate in Banjir Kanal Timur Semarang coastal water during transition of dry season to rainy season was 0.35 cm/month.